2017
DOI: 10.1089/dna.2017.3783
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Suppresses the Prostate Cancer LNCaP Cell Growth and Invasion by Promoting DNA Damage Response Under Oxidative Stress

Abstract: Aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that interacts with multiple signaling pathways during prostate development. In the present study, LNCaP cells were knocked down of AhR by siRNA, or treated with the AhR agonist 3-methylcholanthrene (3MC). The effects of AhR on LNCaP cells and the associated mechanisms were studied both under normal condition and under hydrogen peroxide (HO)induced oxidative stress. MTT, transwell chamber assays and flow cytometry were employed to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…(Al-Dhfyan et al, 2017;Baker & Sakoff, 2020;Donovan et al, 2018;Guarnieri, 2020;Peng et al, 2009;Tsay et al, 2013). Consistent with these findings, in our previous studies, we found that AhR aggravates the PCa progression (Yu et al, 2017(Yu et al, , 2018.…”
supporting
confidence: 92%
“…(Al-Dhfyan et al, 2017;Baker & Sakoff, 2020;Donovan et al, 2018;Guarnieri, 2020;Peng et al, 2009;Tsay et al, 2013). Consistent with these findings, in our previous studies, we found that AhR aggravates the PCa progression (Yu et al, 2017(Yu et al, , 2018.…”
supporting
confidence: 92%
“…The top ranked overrepresented pathway [-log( p -value 5.19)] includes the Aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor that interacts with multiple signaling pathways during prostate development. AHR suppresses the viability and migration of human prostate cancer LNCaP cells (Yu et al, 2017), and plays pivotal role in cancer by modulating the downstream expression of Mitogen-Activated Protein Kinase Kinase Kinase 12 (MAP3K12) (Yu et al, 2018). AHR plays an important role in cellular homeostasis and disease development, and the Aryl hydrocarbon receptor nuclear translocator (AHRN) forms a complex with ligand bound AHR during cancer and activates Bax, a central cell death regulator, MAPK, Aldehyde dehydrogenases (ALDHs), Glutathione transferase (GST) and others (Supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The process initiates apoptosis and involves damage to nuclear DNA accompanied by mitochondrial dysfunction 10.1029/2018RG000629 (Frauenstein et al, 2013). There is a general consensus that the AhR of modern humans is implicated in DNA repair (Dittmann et al, 2016;Schreck et al, 2009), tumor suppression (Fan et al, 2010;Yu et al, 2017), epidermal barrier function (Noakes, 2015), skin tanning response, and melanocyte homeostasis (Jux et al, 2011;Luecke et al, 2010). Phylogenetic analysis suggested that the ability of vertebrate AhR to sense xenobiotics was acquired at a late stage of evolution, implying that the driving force for evolutionary conservation of AhR lies not only in its role in xenobiotic metabolism but also in normal cell development (Hahn et al, 2017;Hao & Whitelaw, 2013).…”
Section: The Role Of the Ahrmentioning
confidence: 99%